Evaluation of Antibacterial and Antibiofilm Activities of Fennel Seed Extract Against Methicillin-resistant Staphylococcus aureus - Sahu, Ashish; Parai, Debaprasad; Ram Choudhary, Hari; Singh, Desh D. (Current Bioactive Compounds, 2024)
Background: Antimicrobial resistance against pathogenic bacterial strains is the current problem faced by the world. Medicinal plants are being focussed for new alternatives to routine antibiotics for novel therapeutic and antimicrobial approaches. Objective: In this present study, fennel extract from Foeniculum vulgare plant was investigated against methicillin-resistant Staphylococcus aureus (MRSA). Method: Ethanol extraction of fennel seeds was performed and minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and time-kill curve was studied to find antimicrobial activities. Biofilm eradication was estimated by crystal violet assay. Result: Antimicrobial study showed a MIC of 500 μg/ml and MBC of 1000 μg/ml for fennel extract. Sub-inhibitory concentrations (½ MIC and ¾ MIC) started to kill bacterial cells after the addition of fennel extract at mid-log phase of growth. Test phytochemical eradicated 38.7%, 62.2%, and 76.9% of MRSA biofilm from microtitre plate when added at a concentration of 250 μg/ml, 375 μg/ml and 500 μg/ml, respectively. Conclusion: This study showed different bactericidal and antibiofilm activity of fennel seed extract against MRSA. We suggested that the phytocompound could be a promising candidate and further investigation is needed to isolate the active component of the extract for the management of MRSA.
Keywords: bactericidal activity